The role of redox proteins in the radiotherapeutic response of breast cancer - Abdullah, Nurul Akmaryanti (2019)
Radiotherapy is an effective treatment for many types of cancer including breast cancer. Ionising radiation induces cytotoxicity mainly via the generation of reactive oxygen species (ROS). The overexpression of redox proteins in various tumours, including breast cancer, has been shown to cause multidrug and radioresistance. Targeting redox proteins represents an innovative approach to enhancing the radiosensitivity of tumour cells. The present study aimed to assess how inhibitors of glutathione (GSH) and thioredoxin (Trx) systems can alter the radiosensitivity of breast cancer cells.